PERANAN PEMERINTAH DESA DALAM PEMBANGUNAN INFRASTRUKTUR (Tanjungpura University, 2021)
This study refers to construction in the village of Kalimas, Sungai Kakap sub-district, Kubu Raya district. The village of Kalimas covers a territory of 4565 acres with village detail (711 ha), estates (2185 ha), Talview (239), land agriculture (1370 ha) with such an area of territory, the masses of communities mostly harnessed themselves. In this study, writers use types of descriptive research with a qualitative approach. Data collection techniques with observation, interviews, and documentaries based on research conducted, it was concluded that the village government of Kalimas has managed to build infrastructures such as the construction of road, bridge, the productions of fire facilities, the post and ambulance. It will remain permanently eroded the covid-19 pandemic in Indonesia, building infrastructure in the village of Kalimas is banned because rural funds are being diverted to help stranded communities.